Revealing the nano-structures of low-dimensional germanium on Ag(1 1 0) using XPS and XPD - Kesper, Lukas; Schmitz, Marie; Schulte, Malte G. H.; Berges, Ulf; Westphal, Carsten (Technische Universität Dortmund, 2022)
In this work, we present a structural investigation of sub-monolayer films of germanium on Ag(1 1 0) by means of photoelectron spectroscopy (XPS) and diffraction (XPD), as well as low-energy electron diffraction (LEED). Since the rising progress in the synthesis of various kinds of nanoribbons, also germanium nanoribbons (Ge-NR) have been synthesized on Ag(1 1 0), recently. Here, we focus on their structural evolution and found the formation of two different phases of germanium at coverages of 0.5ML and 0.7ML, differing fundamentally from predicted nanoribbon structures. By means of LEED measurements, we obtained evidence for germanium superstructures which are not aligned along the [1¯¯¯10]-direction, as expected for nanoribbon growth. Using synchrotron-based high-resolution XPS and XPD experiments of the Ge 3d and Ag 3d core-levels, we resolved the local chemical and atomic order of the germanium films. Thus, the strong internal bonding of the buckled germanium film and a weak Van-der-Waals interaction between silver and germanium were discovered. Moreover, XPD-simulations delivered a detailed model of the structural arrangement of the preliminary nanoribbon phase, which also provided an approach to identify the origin of the two chemically shifted components in the Ge 3d signal by applying a component-wise decomposition of the XPD data.
Applied nanoscience;12(7)
Keywords: Photoelectron spectroscopy; Photoelectron diffraction; Germanium; Interface analysis; Nanoribbon; Low-dimensional materials; 530